Development of an application prototype for mobile devices about pregnancy and syphilis in pregnancy as a health education strategy - Oliveira, Andressa Cristina Batista de Lacerda; Morgado, Lina; Dias, Aline Pinho; Caldeira, Ana Katarine de Oliveira; Moura, Ana Beatriz de Almeida Medeiros; Oliveira Júnior, Maurício da Silva (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: Syphilis is a systemic sexually transmitted infection (STI) caused by the bacterium Treponema pallidum. It has chronic evolution and is subject to flare-ups and latency periods when untreated, which can produce the acquired or congenital forms of the disease. It has been acknowledged in 2016 as an epidemic in Brazil. Objective: To identify the information needs of pregnant women regarding syphilis during pregnancy and congenital syphilis, aiming to assist in the development of a technology-mediated educational resource as a strategy to promote health and fight the syphilis epidemic. Methods: The prior knowledge of pregnant women assisted in high-risk prenatal care at the Maternity of Divino Amor in Parnamirim/RN was investigated, in order to identify the information needs of this population and support the development of a prototype of an educational resource in prenatal care services that use technological mediation, education and communication as distance health education strategies. Results: Forty-six pregnant women who demonstrated to have gaps in knowledge about syphilis were assessed with regard to: signs and symptoms of the disease, prevention measures, and vertical transmission. Conclusion: These findings supported the development of a prototype educational resource that intends to be an important source of information for the adoption of preventive health measures, contributing to the learning process of pregnant women, to the improvement of health indicators in this population and the reduction of congenital syphilis cases.